How well do local relations predict gas-phase metallicity gradients? Results from SDSS-IV MaNGA. Issue 2 (31st May 2022) - Boardman, N; Zasowski, G; Newman, J A; Sanchez, S F; Andrews, B; Barrera-Ballesteros, J K; Lian, J; Riffel, R; Riffel, R A; Schaefer, A; Bundy, K
ABSTRACT: Gas-phase metallicity gradients in galaxies provide important clues to those galaxies' formation histories. Using SDSS-IV MaNGA data, we previously demonstrated that gas metallicity gradients vary systematically and significantly across the galaxy mass–size plane: at stellar masses beyond approximately 10^10 M_, more extended galaxies display steeper gradients (in units of dex/ R e ) at a given stellar mass. Here, we set out to develop a physical interpretation of these findings by examining the ability of local ∼kpc-scale relations to predict the gradient behaviour along the mass–size plane. We find that local stellar mass surface density, when combined with total stellar mass, is sufficient to reproduce the overall mass–size trend in a qualitative sense. We further find that we can improve the predictions by correcting for residual trends relating to the recent star formation histories of star-forming regions. However, we find as well that the most extended galaxies display steeper average gradients than predicted, even after correcting for residual metallicity trends with other local parameters. From these results, we argue that gas-phase metallicity gradients can largely be understood in terms of known local relations, but we also discuss some possible physical causes of discrepant gradients.